ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI TERAPI MUSIK TERHADAP PENURUNAN SKALA NYERI PADA PASIEN DENGAN VENTILATOR DI INTENSIVE CARE UNIT RS BHAYANGKARA TK. I R. SAID SUKANTO - Sitti Latifah Faradiba Suaidy (2022)
Pain is an unpleasant sensory and emotional experience as a result of actual and potential tissue damage, which hurts the body. Pain is a universal problem and is a matter of particular concern for mechanically ventilated patients in the ICU, because these patients require intensive care and undergo various invasive procedures while mechanically ventilated patients cannot communicate their pain verbally. One of the therapies that can be done in dealing with pain in patients who cannot communicate their pain independently is music therapy. The purpose of this study was to determine the effectiveness of music therapy on reducing pain scale. The number of respondents from this study amounted to 2 people with one person being given the intervention while the other one was not given the intervention. The measuring instrument used to assess pain scale in patients with mechanical ventilation using the Critical Pain Observation Tool (CPOT). The type of music used is low tempo instrumental music with 60-80 beats per minute (bpm). The results of the analysis after being given music therapy, it was found that there was a difference in the pain scale between patients who were given the intervention and those who were not. Music therapy is effective in reducing pain scale in critically ill patients with mechanical ventilation, so it is recommended to do it together with pharmacological therapy